Who's in the tub? - Jones, Sylvie Michelle (Blue Apple Books : Distributed in the U.S. by Chronicle Books, 2007)
Willie John Jones is stalling before taking his bath, but when a variety of animals join him, his mother has a hard time getting him out of the bathtub.